Factors Affecting Employee Job Performance at Le Bel Air Resort Hotel - Douangsavanh, Phoyphailin (Souphanouvong University Journal Multidisciplinary Research and Development, 2026)
This study aimed to: (1) examine the level of factors affecting employee job performance at Le Bel Air Resort; (2) assess the level of employee job performance; and (3) identify the factors influencing employee job performance at the resort. A quantitative research approach was employed using a sample of 99 employees selected from Le Bel Air Resort. Data were collected through a structured questionnaire with a high reliability coefficient (Cronbach's Alpha = 0.979). Statistical analyses included frequency, percentage, mean, standard deviation, and Multiple Regression Analysis. The findings indicated that overall factors affecting employee job performance were rated at a moderate level (μ = 3.04, σ = 0.92). Quality of work life was also evaluated at a moderate level (μ = 3.01, σ = 0.91), with adequate and fair compensation receiving the highest mean score, followed by social relationships, and career advancement and job security. Similarly, employee attitudes toward job performance were at a moderate level (μ = 3.08, σ = 0.94), comprising organizational commitment, job satisfaction, and participation in work performance. The overall level of employee job performance was moderate (μ = 3.05, σ = 0.87), with work quality ranking highest, followed by job knowledge and understanding, and achievement of work objectives. Multiple regression analysis revealed that only three variables significantly and positively influenced employee job performance: adequate and fair compensation, responsibility toward job duties, and organizational commitment, with significance levels of 0.01, 0.01, and 0.05, respectively. In contrast, career advancement and job security, social relationships at work, and job satisfaction did not have a statistically significant effect on employee job performance at the 0.05 level.